Teaching Visual Grounded Theory - Konecki, Krzysztof T. (Qualitative Sociology Review, 2009)
The paper is based on personal 20-years experience of teaching methodology of grounded theory and qualitative methods. In the following paper I would like to show the usefulness of visual analysis in teaching methodology of grounded theory. A very important tool is to use pictures and a sequencing of pictures, which give a comparative insight into empirical data and teaches the comparative method that is so important to generate theory (Glaser 1965; Glaser, Strauss, 1967; Glaser 1978). Students can learn how to compare and find patterns in empirical instances, which have visual character. Some of the sequences show stages of action and the sequence that all together is a linear representation of activity. Sequence of pictures helps to build the pattern that is conceptual understanding of the phenomena being studied. In other case, the sequences of pictures given to students are not planned. They are almost accidentally created and force students to find patterns by means of the comparative analysis. We should always know what had happened before a picture was taken as well as afterwards, it is similar to sequences analysis in textual data (Silverman 2007). We should always be aware of the context of analyzed activity. Students are also encouraged to make a theoretical sampling and saturate categories using data from photos and other visual data. This helps them to proceed with the research from empirical incidents to conceptually elaborated properties of categories and finally to the definition of category and formulating the hypotheses. In this way they learn visual grounded theory that is using the visual images for generating categories, properties and hypotheses and also for presenting results of analysis in the final report.